HUBUNGAN USIA IBU BERSALIN DENGAN PERSALINAN SECTIO CAESAREA DI RUMAH SAKIT PANTI WALUYO PURWOREJO - Wulandari, Fetty; Fatmasari, Nawang (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
To suppress the high mortality rate for mothers and fetuses during labor, various efforts are made. One way that can be done is delivery by surgery, namely sectio caesare. A preliminary study at Panti Waluyo Purworejo Hospital in January-October 2021, there were 145 mothers giving birth. Of these deliveries, 68 people (46.9%) underwent caesarean section, consisting of 49 people at risk (84.5%), 19 people at no risk (21.8%). The purpose of this study was to determine the relationship between maternal age and caesarean section delivery at Panti Waluyo Hospital, Purworejo. This research method is an analytic survey with a retrospective approach to sampling with total sampling, statistical tests using the chi square SPSS 2023. The population in this study were mothers who gave birth in January-October 2021. Sampling using purposive sampling technique. Research time in May 2022. Data analysis using chi-square test obtained p value 0.000 which means p value <0.05 so ho is accepted and ha is rejected so that there is a relationship between maternal age and caesarean section delivery at Panti Waluyo Hospital, Purworejo